EMPLOYEE PERFORMANCE OF HUNAN POWER COMPANY VIA COMPETENCY MODEL - Long QiZhou; Suwatana Tungsawat; Supot Rattanapun (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
With the rapid development of information technology and the arrival of the knowledge economy era, competition among enterprises is becoming increasingly fierce. To gain better development opportunities and advantages, more and more enterprises realize that a solid human resource base must be ensured for sustainable and stable development. The current performance management system of Chinese power enterprises has simple and rough assessment contents, which do not consider the differences in employee performance achievement as knowledge carriers, cannot fully motivate employees' productivity and creativity, and cannot ensure the achievement of company strategic goals. Based on the theory of competency model, this study constructs a competency model for power company employees based on the situation, deconstructing employees' competency into three dimensions: core ability, professional ability, and leadership ability. Through a questionnaire survey of 398 employees of Hunan Power Company, this study analyzes the impact of the above three dimensions on employee performance.